2001
DOI: 10.1128/jvi.75.1.11-18.2001
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus Vectors with an Inactivated Gamma Interferon Receptor Homolog Gene (B8R) Are Attenuated In Vivo without a Concomitant Reduction in Immunogenicity

Abstract: The vaccinia virus (VV) B8R gene encodes a secreted protein with homology to the gamma interferon (IFN-␥) receptor. In vitro, the B8R protein binds to and neutralizes the antiviral activity of several species of IFN-␥, including human and rat IFN-␥; it does not, however, bind significantly to murine IFN-␥. Here we report on the construction and characterization of recombinant VVs (rVVs) lacking the B8R gene. While the deletion of this gene had no effect on virus replication in vitro, rVVs lacking the B8R gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 53 publications
4
75
1
Order By: Relevance
“…These results are consistent with an important role for IFN-␥ in the host response and suggest that the vIFN-␥-R homolog may be more important locally for dampening the host response at the primary site of replication rather than for neutralizing systemic IFN-␥. Inactivation of the vIFN-␥-R homolog (B8R) in vaccinia virus resulted in an attenuated phenotype in one study (38) but was found to have no effect on virus virulence in another (39), further illustrating the complex role of the homolog. Because ECTV is a natural mouse pathogen and the vIFN-␥-R homolog it encodes specifically binds to mouse IFN-␥, this is an ideal model to clarify the complex role of this protein in virus-host interactions.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with an important role for IFN-␥ in the host response and suggest that the vIFN-␥-R homolog may be more important locally for dampening the host response at the primary site of replication rather than for neutralizing systemic IFN-␥. Inactivation of the vIFN-␥-R homolog (B8R) in vaccinia virus resulted in an attenuated phenotype in one study (38) but was found to have no effect on virus virulence in another (39), further illustrating the complex role of the homolog. Because ECTV is a natural mouse pathogen and the vIFN-␥-R homolog it encodes specifically binds to mouse IFN-␥, this is an ideal model to clarify the complex role of this protein in virus-host interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms are also proposed for the E3L and K3L gene product to antagonize the IFN pathway. Vaccinia vector lacking B8R was shown to be less toxic to immunocompetent and athymic mice (Verardi et al, 2001). In addition, no concomitant reduction in immunogenicity was observed.…”
Section: Viral Mutants Interfering With the Ifn/pkr Pathwaymentioning
confidence: 93%
“…Intraperitoneal inoculation of immunodeficient mice is an established model for studying disseminated VV infection (14,15,(17)(18)(19). We demonstrated that nude mice inoculated with vNef157 survived significantly longer than those inoculated with vNef1A11 and v50 (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…The expression of Nef157 may have retarded viral replication by reducing virus spread, ultimately resulting in increased time of survival. Furthermore, the murine intranasal model of VV infection has previously been reported to be a sensitive route for the study of pathogenesis and virulence (14,15,20). Immunocompetent CB6F 1 mice inoculated with v50 and vNef1A11 displayed significant weight loss compared with mice inoculated with vNef157, although mice infected with vNef1A11 recovered from weight loss faster than those infected with v50 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation